User Satisfaction Analysis of University of Jember's UC3 using EUCS Approach - Fadhil, Martiana Kholila; Darmawan, Muhammad Riza (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The UC3 service is the University of Jember's integrated digital platform, facilitating academic services including diploma applications, service complaints, and campus problem reporting. Despite being crucial for digital academic administration, the UC3 application encounters technical obstacles such as frequent server downtime, less intuitive interfaces, and slow response times. This study aims to evaluate user satisfaction levels with the UC3 application to provide insights for service improvement and benefit optimization for users. A quantitative methodology was adopted using the End User Computing Satisfaction (EUCS) method, incorporating five variables: content, accuracy, format, ease of use, and timeliness. Data were collected through questionnaires distributed to 100 student respondents and analyzed using IBM SPSS version 27. The instrument test results showed an average validity score of 0.807 and reliability of 0.892 across all EUCS variables. Classical assumption testing confirmed normally distributed data (0.137, p > 0.05), with tolerance values of 0.699 > 0.1 for multicollinearity and no heteroscedasticity detected. Hypothesis testing revealed that accuracy and timeliness had partially significant effects on user satisfaction based on the T-test, while the F-test demonstrated that all EUCS variables collectively had significant influence on satisfaction levels (sig 0.001 < 0.05).The results indicate that UC3 users demonstrate relatively high satisfaction levels, as all EUCS variables significantly influence their experience both individually and collectively, providing a foundation for targeted system improvements.